The Characteristics of Art Paper Produced from Palm Oil Empty Fruit Bunches at Different Cooking Temperatures - Cholilie, Irvan Adhin; Pratama, Tcyo Febry Bayu; Halim, Abdul; Setyaningrum, Paramita; Setiawan, Wahyu Kamal (Green Engineering Society, 2024)
The demand for paper grows yearly, but it's getting harder to get raw materials made of wood, so we need alternate raw materials. The artistic appearance of art paper is one with many distinct and natural tones. Since cellulose fibers from trees are typically used in the production of art paper, this has an effect on deforestation, which contributes to natural disasters. Papermaking was done as part of this study in May–June 2022 at the Semen Indonesia International University's material analysis lab. The goal of the study is to ascertain the impact of pre-treatment and cooking temperature on the caliber of paper produced from empty fruit bunches and paper trash. The variables used in this study were cooking temperatures of 80oC, 90oC, and 100oC. Parameters observed were appearance, grammage, thickness, moisture content, and water absorption on paper. The results showed that the difference in cooking temperature of empty oil palm fruit bunches affected the quality of the paper produced. The highest grammage was obtained in the cooking treatment with a temperature of 80oC, which was 208.83 g/m², the highest paper thickness was obtained in the first treatment (A) at 80oC cooking at 0.16 mm, the highest water content was obtained in the cooking treatment with temperature of 80oC is 4.27%, and the lowest water absorption is obtained in the cooking treatment with a temperature of 80oC which is 314.03%, but the fiber characteristics are still stiff.